Erythropoietin reduces fat mass in female mice lacking estrogen receptor alpha - Jeeyoung Lee; Mary F. Walter; Kenneth S. Korach; Constance Tom Noguchi (Elsevier, 2021)
Objective: Erythropoietin (EPO), the cytokine required for erythropoiesis, contributes to metabolic regulation of fat mass and glycemic control. EPO treatment in mice on high-fat diets (HFD) improved glucose tolerance and decreased body weight gain via reduced fat mass in males and ovariectomized females. The decreased fat accumulation with EPO treatment during HFD in ovariectomized females was abrogated with estradiol supplementation, providing evidence for estrogen-related gender-specific EPO action in metabolic regulation. In this study, we examined the cross-talk between estrogen mediated through estrogen receptor α (ERα) and EPO for the regulation of glucose metabolism and fat mass accumulation. Methods: Wild-type (WT) mice and mouse models with ERα knockout (ERα−/−) and targeted deletion of ERα in adipose tissue (ERαadipoKO) were used to examine EPO treatment during high-fat diet feeding and after diet-induced obesity. Results: ERα−/− mice on HFD exhibited increased fat mass and glucose intolerance. EPO treatment on HFD reduced fat accumulation in male WT and ERα−/− mice and female ERα−/− mice but not female WT mice. EPO reduced HFD increase in adipocyte size in WT mice but not in mice with deletion of ERα independent of EPO-stimulated reduction in fat mass. EPO treatment also improved glucose and insulin tolerance significantly greater in female ERα−/− mice and female ERαadipoKO compared with WT controls. Increased metabolic activity by EPO was associated with browning of white adipocytes as shown by reductions in white fat-associated genes and induction of brown fat-specific uncoupling protein 1 (UCP1). Conclusions: This study clearly identified the role of estrogen signaling in modifying EPO regulation of glucose metabolism and the sex-differential EPO effect on fat mass regulation. Cross-talk between EPO and estrogen was implicated for metabolic homeostasis and regulation of body mass in female mice.